2011
DOI: 10.1111/j.1365-2052.2011.02219.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism identification in the goat KITLG gene and association analysis with litter size

Abstract: This study reported the analysis of KIT ligand (KITLG) gene polymorphisms in 681 goats of three breeds: Xinong Saanen (SN), Guanzhong (GZ), and Boer (BG). In addition, the study identified three allelic variants: g.769T>C and g.817G>T in SN and GZ breeds, and g.9760G>C in the three goat breeds. The g.769T>C and g.817G>T loci were closely linked (r(2) > 0.33). All the single nucleotide polymorphism loci were in Hardy-Weinberg disequilibrium (P < 0.05). Significant associations were found for litter size with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…The litter size traits are intricate quantitative traits involving multiple genes and interactions (An et al, 2013a), so it is important to analyze the inner connection of different genes. Previous studies detected that many genetic mutations within candidate genes could affect goat litter size traits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The litter size traits are intricate quantitative traits involving multiple genes and interactions (An et al, 2013a), so it is important to analyze the inner connection of different genes. Previous studies detected that many genetic mutations within candidate genes could affect goat litter size traits.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic polymorphism of KISS1 gene was explored and showed that four SNPs may affect litter size in goats (An et al, 2015a). Polymorphisms of GNRH1 and GDF9 genes were identified, and their association with litter size in goats was analyzed (An et al, 2013a). The SNPs of the PRLR gene regulated by bta-miR-302a associated with litter size in goats were analyzed (An et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, few studies have identified KITLG as a candidate gene of reproductive traits in animals; the KITLG gene is implicated in animal reproduction (An et al . ; Yao et al . ).…”
Section: Least Square Means and Standard Errors Of The Litter Size Ofmentioning
confidence: 99%
“…In Chinese goat breeds, the association between litter size and a wide array of polymorphisms mapping to the BMP4 [71], CART [72], GDF9 [73,74], GNRH1 [74], INHA and INHBA [75], KISS1 [76][77][78], KITLG [79], POUF1 [80], and TSHB [81] genes, amongst others, has been screened. However, the most significant finding in the field of caprine reproduction genetics has been the elucidation of the molecular basis of the goat polled intersex syndrome (PIS).…”
Section: Candidate Genes For Reproduction Traitsmentioning
confidence: 99%